A Systematic and Comprehensive Analysis for Recommendation of Proposed IoT-Enabled Smart Indoor Hydroponic System Model in Smart Cities - Hooda, Reena; Singh, Sujit Kumar; Nitin; Shivani; Raval, Prachi; Singh, Chandan (International Journal of Basic and Applied Sciences, 2025)
Rapid population growth and changes in climate have resulted in the depletion of arable lands and require a solution. Hydroponic cultivation is one such solution that uses the approach of soilless smart farming. It requires considerable effort to maintain favorable environmental conditions and provide appropriate nutrition to plants. IoT technology helps in automating all the required processes for better cultivation of crops. IoT helps in enhancing the productivity and cost-effectiveness of growing plants by minimizing the interference of human beings. IoT sensors assist the users in obtaining real-time data to optimize the growth of plants, improve the quality of food, and lessen the cost of production. Smart farming in urban areas has acquired huge popularity as it improves the lifestyle of people by introducing indoor hydroponic farming systems in smart buildings. This type of system needs less space and can be set up inside a room. It makes use of IoT sensors for monitoring the environmental conditions, such as the pH value, temperature, humidity, light control, nutrient control, and soil moisture control, to ensure better and quicker growth of crops and better quality yields. In this paper, a Smart Indoor Hydroponic System for precision farming in smart cities using IOT and AI is proposed that takes less space and provides better quality crops without any human intervention by making use of IoT sensors.
Keywords: Artificial Intelligence (AI); Hydroponic System; Internet of Things (IoT); Precision farming; Smart city